2007
DOI: 10.1016/j.biopsych.2006.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Functional Connectivity in Major Depression: Abnormally Increased Contributions from Subgenual Cingulate Cortex and Thalamus

Abstract: Background: Positron emission tomography (PET) studies of major depression have revealed resting-state abnormalities in the prefrontal and cingulate cortices. Recently, fMRI has been adapted to examine connectivity within a specific resting-state neural network-the default-mode network -that includes the medial prefrontal and anterior cingulate cortices. The goal of this study was to examine resting-state, default-mode network functional connectivity in subjects with major depression and in healthy comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

125
1,529
21
15

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,038 publications
(1,690 citation statements)
references
References 66 publications
125
1,529
21
15
Order By: Relevance
“…We demonstrate in preHD that depression scores are positively correlated with the functional connectivity of a brain module which includes the precuneus, isthmus cingulate, inferior parietal, hippocampus, parahippocampal gyrus, entorhinal, temporal pole, rostral anterior cingulate, and medial orbitofrontal. These regions are found in the default mode brain network [Buckner et al, 2008], which shows increases in functional connectivity in those with MDD [Greicius et al, 2007]. The DMN can be further sub‐divided into anterior and posterior components.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate in preHD that depression scores are positively correlated with the functional connectivity of a brain module which includes the precuneus, isthmus cingulate, inferior parietal, hippocampus, parahippocampal gyrus, entorhinal, temporal pole, rostral anterior cingulate, and medial orbitofrontal. These regions are found in the default mode brain network [Buckner et al, 2008], which shows increases in functional connectivity in those with MDD [Greicius et al, 2007]. The DMN can be further sub‐divided into anterior and posterior components.…”
Section: Discussionmentioning
confidence: 99%
“…Many publications have focused on analysing the default-mode network (DMN) (Buckner et al, 2008), a set of regions highly synchronised during rest. This methodology has been used in several diseases characterised by diffuse lesions (Fox and Greicius, 2010) such as schizophrenia (Jafri et al, 2008), Alzheimer's disease (Li et al, 2002;Greicius et al, 2004) or depression (Greicius et al, 2007), but investigations in MS are limited to relatively fewer publications. For example, Cover et al (2006) found decreased inter-hemispheric connectivity in MS patients at rest, using a coherence measure based on magneto-encephalography (MEG).…”
mentioning
confidence: 99%
“…A decrease in connectivity at T  = 4.5 h between the default mode network and precuneus, PCC and ACC is in line with earlier results [Klaassens et al, 2015; McCabe and Mishor, 2011; McCabe et al, 2011; Van de Ven et al, 2013; Van Wingen et al, 2014] and in agreement with opposite features in depression, which is characterized by increased connectivity of DMN components [Sundermann et al, 2014]. Especially the posterior part of the DMN, where citalopram effects were most prevalent, has been implicated in SSRI efficacy in depression [Greicius et al, 2007; Li et al, 2013]. Furthermore, consistent with an increased cerebellar‐DMN connectivity in depression [Sundermann et al, 2014], citalopram reduced connectivity between the DMN and cerebellum.…”
Section: Discussionmentioning
confidence: 98%